Highway Maintenance Management: A Review of Some Practices in Malaysia - Ghani, Arif; Mad Lazim, Halim; Lamsali, Hendrik; Salleh, Mohamed Najib (UUM Press, 2017)
Highway maintenance is becoming a very popular topic in recent years. The relationship between the growth of the nation and welfare of the society has highlighted the importance of the subject. Without the proper maintenance system, highways can rapidly tumble into depreciation which in the end will affect the highways patron in term of vehicle operation, time, reliability and safety. With the alarming number of accidents happened due to highway condition, the effectiveness of the highway maintenance management system in Malaysia has raised a concerned. A study conducted to address this issue with related government agencies, highway operators and highway personnel using qualitative approach